2009
DOI: 10.3892/ijmm_00000249
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutated cell line with characteristics of dedifferentiated chondrosarcoma

Abstract: Abstract. Dedifferentiated chondrosarcoma (CS) is a rare, highly malignant variant of CS in which a high-grade sarcoma coexists with a low-grade chondroid tumor. In this study, a novel dedifferentiated CS cell line, MS0812, was spontaneously established from mutated human embryonic muscle cells. Several features of the cell line were investigated, including growth characteristics, cytogenetics, electron microscopic features, expression of various antigenic markers and tumor formation. MS0812 has been cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It might be associated with the activation of oncogenes and inactivation of tumor suppressor genes, such as the amplification of c-myc and the inactivation of CDKI family (6,8,14,21). We found that human embryonic muscle cells cultured in vitro long-term could become immortalized spontaneously, and have obtained 6 novel cell lines (10). This type of tumor cell lines expressed actin, vimentin and desmin in vitro, which suggest that these malignant cells were originated from embryonic muscle cells, and these cell lines could develop sarcoma in nude mice (10).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…It might be associated with the activation of oncogenes and inactivation of tumor suppressor genes, such as the amplification of c-myc and the inactivation of CDKI family (6,8,14,21). We found that human embryonic muscle cells cultured in vitro long-term could become immortalized spontaneously, and have obtained 6 novel cell lines (10). This type of tumor cell lines expressed actin, vimentin and desmin in vitro, which suggest that these malignant cells were originated from embryonic muscle cells, and these cell lines could develop sarcoma in nude mice (10).…”
Section: Discussionmentioning
confidence: 87%
“…We found that human embryonic muscle cells cultured in vitro long-term could become immortalized spontaneously, and have obtained 6 novel cell lines (10). This type of tumor cell lines expressed actin, vimentin and desmin in vitro, which suggest that these malignant cells were originated from embryonic muscle cells, and these cell lines could develop sarcoma in nude mice (10). However, malignant transformation mechanism in gene level is not clear yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…p16 regulates cell cycle through the inhibition of cdk4 and cdk6 32. Analysis of a dedifferentiated chondrosarcoma cell line, MS0812, suggests that deletion of the p16 gene may play a major role in the malignant phenotype of dedifferentiated chondrosarcoma 12. Moreover, aberrant promoter methylation of the p16 gene has also been reported in both components of dedifferentiated chondrosarcoma 25.…”
Section: Discussionmentioning
confidence: 99%